A new approach for evaluating maize transgressive segregants and their three-way cross potential in the S4 convergent breeding population - Nuniek Widiayani; Muhammad Fuad Anshori; Nasaruddin Nasaruddin; Muh Farid; Ifayanti Ridwan; Abd. Haris Bahrun; Muhammad Azrai; Amin Nur; Purnama Isti Khaerani; Willy Bayuardi Suwarno; Karlina Syahruddin; Naeem Khan; et al. (BMC Plant Biology)
Abstract The development of transgressive segregant (TS) selection on convergent breeding populations of S4 maize is a concept that is rarely applied. However, the development of TS is necessary to accelerate maize breeding pipelines. Therefore, the objectives of this study were (1) to develop the concept of TS selection and (2) to select S4 TS maize to be developed as hybrid cross parents. The study was carried out using two experiments. The first experiment was designed with an augmented design of 6 replications for control genotypes. This design is just one factor focused on maize genotypes. However, it was divided into two sets: non-replicated of 32 TS lines and replicated of four check hybrid varieties. The second experiment focused on validation using a three-way cross. The experiment used a randomized complete block design with three replications. Based on the resulting study, the combination of ratio analysis, path analysis, best linear unbiased prediction, relative fitness, and selection indices is an objective approach to assessing the genetic potential of the S4 TS. The selection index formed was 0.53 ear weight + 0.24-grain yield percentage + yield. The index selection resulted in 11 S4 TS lines being further evaluated for their hybrid potential, with the TS line CB2.23.1 being the best. However, these TSs are expected to focus on identifying and combining ability through diallel crosses in the future. Furthermore, the three-way cross hybrid lines assessment also revealed SG 3.35.12 × JH37 F1 and CB 2.23.1 × JH37 F1 to be promising hybrid lines.